Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian pada Produk Mi Instan Sarimi (Studi pada Mahasiswa yang Sedang Kuliah di Surabaya) - Khoirunnisa' Islamiyah; Ugy Soebiantoro (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of beauty influencers and product quality on purchasing decisions for Instant noodles are one of the most popular food businesses in Indonesia because it favored by many people. This condition makes instant noodles companies in Indonesia increasingly vying to win the market competition, such as Sarimi. This study aims to analyze the effect of brand image and product quality on purchase decisions. The variables in this study consisted of brand image (X1), product quality (X2), and purchase decisions (Y). This research aimed at college students who are currently studying in Surabaya with a total sample of 96 respondents. The sampling technique in this study is a non-probability sampling technique with a purposive sampling approach. The data analysis technique used is Partial Least Square (PLS) and processed with SmartPLS 3.0 software. The results indicate that brand image has a positive and significant effect on purchase decisions, and product quality has a positive and significant effect on purchase decisions.